Food aid programme during restricted hilsa fishing period: effectiveness and management perspective - Mredul, Md. Mahamudul Hasan; Uddin, Md. Ektear; Pervez, A K M Kanak; Yesmin, Farhana; Akkas, Antara Binte (Journal of Fisheries, 2020)
Hilsa (Tenualosa ilisha) is geographically and economically important species in Bangladesh. To conserve hilsa, the government of Bangladesh has introduced fishing ban for certain periods of the year and also provides food assistance to hilsa fishers during the restriction period. Inadequate management often pushes real fishers out of the assistance programme and therefore, this study focused on assessing the effectiveness of the programme with a view to proposing a better management practice. A total of 202 randomly selected fishermen, living in the villages adjacent to Andharmanik River of Patuakhali district of Bangladesh, were interviewed. The Andharmanik River is famous for the natural breeding of hilsa. Results suggest that the amount of food provided and its distribution pattern were not that effective for the fishermen. Effectiveness was significantly related to the number of earning able family member, income difference between peak and restricted season and loan facility during the restriction period. This study also explained income difference trajectories of the fishermen community. Community-based management with facilitation by the state fisheries department and local government entity may enhance the programme effectiveness. More awareness programme and research are needed in this regard.